Enhanced generalized modeling method for compliant mechanisms: Multi-Compliant-Body matrix method - Lim, Hyunho; Choi, Young Man (Structural Engineering and Mechanics, 2022)
The multi-rigid-body matrix method (MRBMM) is a generalized modeling method for obtaining the displacements, forces, and dynamic characteristics of a compliant mechanism without performing inner-force analysis. The method discretizes a compliant mechanism of any type into flexure hinges and rigid bodies by implementing a multi-body mass-spring model using coordinate transformations in a matrix form. However, in this method, the deformations of bodies that are assumed to be rigid are inherently omitted. Consequently, it may yield erroneous results in certain mechanisms. In this paper, we present a multi-compliant-body matrix-method (MCBMM) that considers a rigid body as a compliant element, while retaining the generalized framework of the MRBMM. In the MCBMM, a rigid body in the MRBMM is segmented into a certain number of body nodes and flexure hinges. The proposed method was verified using two examples: the first (an XY positioning stage) demonstrated that the MCBMM outperforms the MRBMM in estimating the static deformation and dynamic mode. In the second example (a bridge-type displacement amplification mechanism), the MCBMM estimated the displacement amplification ratio more accurately than several previously proposed modeling methods.
Keywords: Compliant bodies; Dynamics analysis; Finite element method; Flexure hinge; Generalized models; Matrix methods; Model method; Multi-rigid-body; Quasi-static; Rigid body; compliant mechanism; dynamic analysis; Finite Element Method (FEM); numerical methods; quasi-static; structural design